The revision of fossil big-eyed bugs suggests a peculiar evolutionary history of a peculiar true bug family (Heteroptera: Lygaeoidea: Geocoridae) (vol 103, pg 531, 2023) - Kobor, Peter; Faundez, Eduardo I.; Roca-Cusachs, Marcos (My University, 2024)
There has to be a correction in the acknowledgements for figure 5: The photos in Figure 5 (Fig. 5. Geocoris (Geocoris) monserrati Ortuño and Arillo, 1997 (holotype): a overview of fossil; b dorsal half; c ventral half (scale bar = 1 mm for images b and c). were done by José-Carmelo Corral, PhD, external employee at the Museo de Ciencias Naturales de Álava (Alava Museum of Natural Sciences), Vitoria-Gasteiz, Spain. The authors declare, that they acted in good faith and were unaware that the photographer was not acknowledged. The authors apologise for any inconvenience and hereby express their gratitude to Dr. Corral for the photos of the types of G. monserrati.
Keywords: Fossil Record